Validação de metodologia analítica por cromatografia líquida de alta eficiência para quantificação de bupivacaína (S75-R25) em nanoesferas de poli(lactídeo-co-glicolídeo) - Moraes, Carolina Morales; Paula, Eneida de; Rosa, André Henrique [UNESP]; Fraceto, Leonardo Fernandes [UNESP] (Sociedade Brasileira de Química, 2008)
Bupivacaine (S75-R25, NovaBupi®) is an amide type local anesthetic widely used. The present work consists of the development and validation of analytical methodology for evaluation of NovaBupi® content in the poly-lactide-co-glycolide nanospheres (PLGA-NS) by high performance liquid chromatography. The separation was made using the reversed-phase column LC-18, acetonitrile/phosphate buffer 85:15 v/v as mobile phase and detection at 220 nm. The results obtained show that the analytical methodology is accurate, reproducible, robust and linear over the concentration range 10-220.0 g/mL of NovaBupi®. The method was applied to determine the encapsulation efficiency and evaluate the release profile of NovaBupi®, showing good results.
Validation of analytical methodology by HPLC for quantification of bupivacaine (S75-R25) in poli-lactide-co-glicolide nanospheres
Keywords: bupivacaine; PLGA nanospheres; HPLC